2014
DOI: 10.1080/13825585.2014.933770
|View full text |Cite
|
Sign up to set email alerts
|

Fear of falling and falls in older adults with mild cognitive impairment and Alzheimer’s disease

Abstract: Cognitive impairment and fear of falling are risk factors for falls in older adults. Recurrent falls are more prevalent in older adults with cognitive impairment. We examined the number of previous falls, self-reported fear of falling, and the Falls Efficacy Scale-International (FES-I) in 104 older adults [26 with mild Alzheimer's disease (AD), 42 with mild cognitive impairment (MCI) and 36 cognitively healthy]. Older adults with AD and MCI had a higher number of falls (1.1 ± 1.2 and 1.5 ± 1.5, respectively) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(73 citation statements)
references
References 62 publications
2
68
0
3
Order By: Relevance
“…Our findings of variables predicting an association with cognitive impairment build upon previous work among older adults (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). In this study, self-reported hypertension was not a significant predictor of cognitive impairment.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Our findings of variables predicting an association with cognitive impairment build upon previous work among older adults (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). In this study, self-reported hypertension was not a significant predictor of cognitive impairment.…”
Section: Discussionsupporting
confidence: 58%
“…Cognitive impairment and dementia have been associated with rural dwellers (16), increased rates of hospitalization (17,18), increased risk for falls (19,20), increased prevalence of fear of falling (21,22), diabetes mellitus (23,24), depression (17,25), and dependence in activities of daily living [ADL] (26). There are conflicting studies on the association of gender and hypertension with cognitive impairment (27)(28)(29).…”
Section: Introductionmentioning
confidence: 99%
“…Recente publicação 32 mostrou que idosos com DA com CDR 1 apresentavam menor medo de cair e maior número de quedas em comparação aos idosos com comprometimento cognitivo leve (CDR 0,5) e idosos saudáveis cognitivamente. De acordo com essa pesquisa, o menor medo de cair associado ao maior número de quedas pode ocorrer devido a uma menor autocrítica e consciência de seus déficits em pacientes com DA.…”
Section: Discussionunclassified
“…De acordo com essa pesquisa, o menor medo de cair associado ao maior número de quedas pode ocorrer devido a uma menor autocrítica e consciência de seus déficits em pacientes com DA. 32 Dessa maneira, pode-se observar que são múltiplas as implicações da consciência da doença em idosos com DA, não apenas em relação à funcionalidade, que é o foco deste estudo, mas em relação ao medo de cair, por exemplo.…”
Section: Discussionunclassified
“…In the present study, we included participants who completed baseline assessments and follow‐up assessments of disability by the national long‐term care insurance (LTCI) system. We excluded participants according to the following criteria: (1) having a disability based on the LTCI system at baseline; (2) a history of Parkinson disease, stroke, depression, or Alzheimer disease; (3) a mini‐mental state examination (MMSE) score below 19; and (4) death or moving to another city during the follow‐up period. After exclusions, data from 4329 individuals were available for analysis in the present study.…”
Section: Methodsmentioning
confidence: 99%